Redescription of Adenomera diptyx (Boettger, 1885) (Anura, Leptodactylidae) and description of a closely related new species - Zaracho, Víctor H.; Lavilla, Esteban O.; Carvalho, Thiago R.; Motte, Martha; Basso, Néstor G. (European Journal of Taxonomy, 2023)
Adenomera is a genus of Neotropical leaf-litter frogs widely distributed in South America and regarded taxonomic-wise challenging. One of these is the open-habitat Adenomera diptyx from Paraguay, which may correspond to a species complex. An integrative analysis of morphological variation, in combination with acoustic and molecular data of several populations from Argentina, Paraguay, and Brazil resulted in the recharacterization of nominal A. diptyx and the description of a new, closely related species. Adenomera diptyx is recognized by its advertisement call given at a high repetition rate (176–299 per minute), and the dorsal color pattern consisting of a light mid-dorsal line and a dark brown interorbital bar with irregular black edges. In comparison with A. diptyx, the new species, Adenomera guarani sp. nov., produces its advertisement call at a lower repetition rate (73–147 per minute), and the dorsal color pattern consists of a light, broad, mid-dorsal stripe and a mask-like patch in the interorbital region. The redefinition of A. diptyx will contribute to future studies focusing on the taxonomic status of other genetic lineages tentatively assigned to this species complex, which could represent additional unnamed species in the open-habitat Adenomera clade.